Nigeria : Selected Issues. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2016)
This paper discusses a few selected issues of the Nigerian economy-options and strategies for a fiscal rule for oil wealth management, enhancing the effectiveness of monetary policy, and recent developments and prospects of capital flow. Despite its diversified economy, Nigeria's fiscal policy is heavily dependent on the oil sector. This paper explores options for a formalized rule-based approach to setting a 'depoliticized' budget oil price. Two boom-and-bust episodes since early 2000 have highlighted the challenges in the current monetary policy framework. Nigeria has also been characterized by sizable capital outflows, which have diminished recently.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet